Awareness of prostate cancer and its associated factors among men 40 years of age and older in Mizan Aman town, Bench Sheko zone, Southern Nations, Nationalities, and Peoples’ Region, South West Ethiopia, 2019 - Assefa, Ashenafi; Germossa, Gugsa Nemera; Ayenew, Mengistu; Bedada, Gadisa Bekele (Frontiers in Oncology, 2022)
Background: Prostate cancer is the common cause of morbidity and mortality among men aged 40 years and older. Evidence has shown that awareness of prostate cancer plays a greater role in the early detection of prostate cancer than anyone else. However, there is paucity of information regarding prostate cancer awareness levels in Ethiopia in general and in Mizan Aman town in particular. Objectives: To assess the awareness of prostate cancer and its associated factors among men aged 40 years and older in Mizan Aman, Bench Sheko Zone, South Nation Nationality People Region, South West Ethiopia, 2019. Methods: A community-based cross-sectional study was conducted from April 1–30, 2021 in Mizan Aman town. A total of 322 study subjects were selected from a total population of 1242 by using the simple random sampling method in Mizan Aman town. Data was collected through a face-to-face interview using a structured questionnaire. Data were entered into Epi Data version 3.1 and analyzed by statistical package for social science version 20. Descriptive statistics were used to summarize socio-demographic characteristics and personal history. Bi-variate and multivariate regression analysis were used to explore further variables that were associated with the level of awareness. Significant associations were declared at a P-value of< 0.05. The results were presented in text, tables, and charts. Results: The magnitude of prostate cancer awareness was 64%. Those participants who had aged between 40 to 55 years (Adjusted Odd Ratio = 6.16, 95% Confidence interval = 2.62–14.47), government employers (Adjusted Odd Ratio = 4.684, 95% Confidence interval = 1.56–13.97), and those whose monthly income level is greater than 5000 birrs (Adjusted Odd Ratio = 12.45, 95% Confidence interval = 12.45 (3.2–47.77) were significantly associated with the level of awareness. Conclusion and recommendation፡ this study revealed that more than half of the men residing in Mizan Aman town had a high level of prostate cancer awareness. First category age, better economic status, and, employment were significantly associated with awareness of prostate cancer. This indicates the need for a collective effort to enhance the awareness of men regarding prostate cancer.